Clinical and functional biochemical characteristics of the oral cavity organs with dentoalveolar anomalies in children and adolescents with bronchial asthma - Gavkharkhon Fazilbekova; Sunnatullo Gafforov (Genius Journals, 2021)
The dental condition of the oral cavity of children and adolescents with dentoalveolar anomalies against the background of bronchial asthma was studied in 225 patients. Of these, 180 with dentoalveolar anomalies and deformity, suffering from bronchial asthma, and 45 patients without somatic pathology in the age categories 6-9 years old, 10-13 years old and 14-18 years old. In the course of clinical research, the state of hard tissues of the tooth, periodontal tissues and oral mucosa, biochemical composition of the oral fluid, morphological parameters of the maxillofacial region, as well as the frequency of dentoalveolar anomalies and deformities were studied. The clinical, functional and biochemical state of the oral cavity in children and adolescents with dentoalveolar anomalies against the background of bronchial asthma was assessed. Also, for further continuation of the research stages to determine the morphological and functional effectiveness of removable and non-removable orthodontic appliances, a study of the hygienic state and biochemical composition of the oral fluid of children and adolescents was carried out
Keywords: Children And Adolescents; Oral Cavity; Bronchial Asthma; Dentoalveolar Anomalies and Deformities